The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1159/000262374
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Plaque pH Changes within the Trough of an in situ Appliance Used to Study Mineral Changes in Early Carious Lesions

Abstract: Plaque pH was measured using a glass combination pH microelectrode of plaque deposits lining the trough of an intra-oral appliance which contained single sections of human teeth with artificial enamel lesions. Plaque exposure to a 10% sucrose solution produced significantly lower plaque pH levels than a solution of sorbitol gum extract. The subsequent flow of saliva over the plaque/pH electrode interface resulted in a significant and rapid increase in pH. Repeat experiments, using deionised water instead of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Controversy still exists in this regard, but it has been shown that acids released from plaque affect every tooth surface [7]. This fact may support the use of different surfaces for plaque collection [1,2,4,7,39 Á/ 41], although lingual surfaces provide an excellent site for plaque accumulation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Controversy still exists in this regard, but it has been shown that acids released from plaque affect every tooth surface [7]. This fact may support the use of different surfaces for plaque collection [1,2,4,7,39 Á/ 41], although lingual surfaces provide an excellent site for plaque accumulation [37].…”
Section: Discussionmentioning
confidence: 99%
“…Lively debate has taken place within the dental caries research community over several decades as to how plaque pH data should be most meaningfully reported. 9,38,67,72,75,129,134 One should be aware that plaque pH data can be presented in a series of ways (such as 'minimum pH', 'pH area' and 'cH area'), which can, put slightly differing emphases of a given set of plaque pH data. This question has been recently re-visited through the use of useful computer programmes in order to clarify this issue.…”
Section: Plaque Ph Parametersmentioning
confidence: 99%